The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.neuroscience.2016.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Gestational stress and fluoxetine treatment differentially affect plasticity, methylation and serotonin levels in the PFC and hippocampus of rat dams

Abstract: Women are more likely to develop depression during childbearing years with up to 20% of women suffering from depression during pregnancy and in the postpartum period. Increased prevalence of depression during the perinatal period has resulted in frequent selective serotonin reuptake inhibitor (SSRI) antidepressant treatment; however the effects of such medications on the maternal brain remain limited. Therefore, the aim of the present study is to investigate the effects of the SSRI medication, fluoxetine, on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 86 publications
1
45
0
4
Order By: Relevance
“…In a series of studies, Pawluski and colleagues have reported that gestational stress affects adult hippocampal neurogenesis and CA3 dendritic structure in pregnant rats (Pawluski et al, 2016). Exposure to chronic stress during pregnancy also reduces spine density and dendritic complexity in the prefrontal cortex and the nucleus accumbens shell (Haim et al, 2014; Leuner et al, 2014; Haim et al, 2016), while it raises synaptophysin levels in the cingulate cortex and increases spine density in the basolateral amygdala of rat dams (Gemmel et al, 2016; Haim et al, 2016). Some of these alterations are reversed by antidepressant treatment (Gemmel et al, 2016; Haim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of studies, Pawluski and colleagues have reported that gestational stress affects adult hippocampal neurogenesis and CA3 dendritic structure in pregnant rats (Pawluski et al, 2016). Exposure to chronic stress during pregnancy also reduces spine density and dendritic complexity in the prefrontal cortex and the nucleus accumbens shell (Haim et al, 2014; Leuner et al, 2014; Haim et al, 2016), while it raises synaptophysin levels in the cingulate cortex and increases spine density in the basolateral amygdala of rat dams (Gemmel et al, 2016; Haim et al, 2016). Some of these alterations are reversed by antidepressant treatment (Gemmel et al, 2016; Haim et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested, in line with the synaptogenic hypothesis of depression (Hajszan et al, 2010), that peripartum stress elicits extensive neuroplasticity in the maternal brain, which potentially contributes to the development of postpartum affective illness (Pawluski et al, 2016). Recent studies are beginning to demonstrate that the maternal nervous system is indeed remodelled by stress both in humans (Moses-Kolko et al, 2014) and in animal models (Gemmel et al, 2016; Haim et al, 2016; Pawluski et al, 2016). Nevertheless, more research is needed to better understand the extent to which neuroplasticity is implicated in stress-related maternal disorders.…”
mentioning
confidence: 99%
“…Humán felmérések (Moses-Kolko et al, 2014) és rágcsálókon végzett kísérletek (Gemmel et al, 2016;Haim et al, 2016;Pawluski et al, 2016) is bizonyítják azt a tényt, hogy a stressznek idegrendszert befolyásoló hatása van a terhesség alatti időszakban, ugyanis a terhesség alatti folyamatos stressz szorongásos viselkedést és a szülői gondoskodás hiányát eredményezte a terhesség után (Darnaudéry et al, 2004;Smith et al, 2004;Brummelte & Galea, 2010). Ez a megfigyelés a depresszió szinaptogenikus hipotézisével összhangban állhat (Hajszan et al, 2010), miszerint a terhesség alatti stressz az idegsejtek specifikus strukturális változását válthatja ki az anya központi idegrendszerében, hozzájárulva a szülést követő megváltozott kedélyállapothoz .…”
Section: A Terhesség Utáni (Posztpartum) Depresszióunclassified
“…Számos, rágcsálókon végzett tanulmány számol be arról, hogy a terhesség alatti tartós stressz a szülést követően szorongásos viselkedést és a szülői gondoskodásban való deficitet okoz (Darnaudéry et al, 2004;Smith et al, 2004;O'Mahony et al, 2006;Brummelte & Galea, 2010;Hillerer et al, 2011). Humán vizsgálatokkal bizonyították, hogy a terhesség alatti időszakban az erős stressz befolyásolja a hippokampális neurogenezist és a CA3 piramissejtek dendritikus morfológiáját , továbbá csökkenti a prefrontális kéregben és a bazális előagyi nucleus accumbens héj régiójában lévő principális sejtek dendrittüskéinek számát és a dendritarborizációjuk sűrűségét (Leuner et al, 2014;Haim et al, 2016), míg növeli a gyrus cinguli kérgi régióban a szinaptofizin szintjét és a bazolaterális amigdalában a dendrittüskék számát (Gemmel et al, 2016;Haim et al, 2016). E változások egy részét antidepresszáns-kezelésekkel vissza lehetett fordítani (Gemmel et al, 2016;Haim et al, 2016).…”
Section: A Stressz Hatása Az Anyai Idegrendszerreunclassified
See 1 more Smart Citation